DSMC data-improved numerical simulation of hypersonic flow past a flat plate in near-continuum regime. (15th November 2019) - Ou, Jihui; Chen, Jie
Highlights: A DSMC data-improved NS model is extended for near-continuum hypersonic flows. The shear induced non-equilibrium effect is well modeled by the proposed method. The method extends the capability of NS solvers in hypersonic rarefied flows. The new model leads to an extra computational cost of 30% compared with the CFD. Abstract: Numerical simulation of hypersonic flows over a flat plate in near-continuum regime is presented to assess a data-improved Navier-Stokes (DiNS) model, which has been developed for modeling flows involving local non-equilibrium effects. The simulation is directly performed in the framework of Navier-Stokes-Fourier (NSF) equations, but with the viscosity coefficient and thermal conductivity coefficient modified according to a certain parameter Zh characterizing the local shear induced non-equilibrium effect, based on data obtained by Direct Simulation Monte Carlo (DSMC) method for typical shear flows. Excellent agreement on both drag and heat transfer coefficients are obtained by the DiNS method compared with solution of the DSMC method. The present DiNS method exhibits remarkable improvement compared with the traditional NSF method in predicting the flow profiles as well as the surface shear stress and heat flux. For the new continuum model, the extra numerical cost, compared with the conventional continuum model, is less than 30%. Hence, our new method, unlike the DSMC method, can readily be applied to engineering problems in regard with the computational cost.